A kind of high oxidation resistance lead-free solder paste and preparation method thereof

By adding bismuth, red phosphorus and germanium to lead-free solder and using specific fluxes and active agents, the problem of easy oxidation of lead-free solder at high temperatures is solved, and solder with high oxidation resistance and wettability is achieved, reducing solder costs.

CN118808986BActive Publication Date: 2025-04-08SHENZHEN VITAL NEW MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411147865.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-21
Publication Date
2025-04-08
Estimated Expiration
2044-08-21

AI Technical Summary

Technical Problem

Existing lead-free solder is prone to tin oxide slag at high temperatures, affecting the welding process and product quality, and leading to an increase in usage cost.

Method used

Add a certain amount of bismuth, red phosphorus and germanium to the lead-free solder, and use rosin and liquid maple as flux, combining dipolymer fatty acids, boric anhydride and triethanolamine as active agents to form a highly antioxidant lead-free solder paste.

Benefits of technology

The amount of oxidation slag of lead-free solder is significantly reduced, the oxidation resistance and wettability of the solder is improved, and the solder costs are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005002716580000011
    Figure BDA0005002716580000011
  • Figure BDA0005002716580000021
    Figure BDA0005002716580000021
  • Figure BDA0005002716580000022
    Figure BDA0005002716580000022
Patent Text Reader

Abstract

The invention relates to a highly anti-oxidation lead-free solder paste and a preparation method thereof, belonging to the technical field of welding materials; the lead-free solder paste comprises components: solder alloy powder, flux, and dispersant; the solder alloy powder comprises components: silver, copper, bismuth, antimony, red phosphorus, germanium, and tin; the flux comprises components: rosin, liquid maple, an activator, an antioxidant, and a solvent; the lead-free solder paste provided by the invention has high anti-oxidation performance and low slag generation rate, and also has good wettability and non-toxicity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of welding materials, and in particular relates to a highly anti-oxidation lead-free solder paste and a preparation method thereof. Background Art

[0002] Tin has excellent properties such as soft texture, low melting point, good ductility, strong plasticity and non-toxicity. It can be combined with many substances to form alloys with different properties and wide applications. Tin-lead solder and lead-free solder used in manual dip soldering, wave soldering, automatic soldering and surface mounting processes in the electronics manufacturing industry account for 70% of tin usage. Due to the serious toxicity of lead and its compounds, which have significant impacts on the environment and human health, the demand for using lead-free solder to replace tin-lead solder is becoming more and more urgent. However, the existing lead-free solder is prone to produce tin oxide slag when used at high temperatures, which affects the welding process and product quality, resulting in increased use costs.

[0003] Therefore, developing a highly antioxidant lead-free solder is of great significance to the application and development of lead-free solder. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention aims to provide a lead-free solder paste having high oxidation resistance, good wettability, non-toxicity and low melting point, and a preparation method thereof.

[0005] To achieve the above object, the present invention discloses the following technical solutions:

[0006] In a first aspect, the present invention discloses a highly anti-oxidative lead-free solder paste, comprising the following components in parts by weight:

[0007] 80-90 parts of welding alloy powder;

[0008] 7-10 parts of flux;

[0009] 3-5 parts of dispersant;

[0010] The solder alloy powder comprises the following components in percentage by mass:

[0011]

[0012]

[0013] Melting point is a very important characteristic of lead-free solder. Adding bismuth to lead-free solder can significantly reduce the melting point of the solder. When the amount of bismuth added is too large, the melting range of the solder will increase, affecting the liquid fluidity of the solder and reducing the wettability of the solder. Therefore, the present invention adds a certain amount of bismuth to the Sn-Ag-Cu system, taking into account the reduction of the overall solder melting point while ensuring its wettability.

[0014] A certain amount of red phosphorus is added to the lead-free solder melt, the main function of which is to utilize its oxygen-affinity effect; red phosphorus can form a dense surface protection film on the surface or sub-surface of the liquid solder through self-oxidation, cut off the contact between the alloy solder and oxygen, reduce the surface tension of the solder solution, and improve wettability; the addition of red phosphorus can change the structure of the tin oxide film, forming a film denser than the tin oxide film, effectively preventing oxygen from entering the lead-free solder melt, and improving the oxidation resistance of the solder; when the amount of red phosphorus added is too much, it will become a harmful impurity, aggravate oxidation, and be detrimental to wettability. Therefore, the preferred amount of red phosphorus added in the present invention is 0.010%-0.015% of the solder alloy powder to achieve a balance between oxidation resistance and wettability.

[0015] Solder oxidized slag is mainly tin dioxide and tin oxide, which are metal ion excess oxides (n-type semiconductors). The growth rate of n-type semiconductor oxide films is controlled by the diffusion of interstitial cations. At the same temperature, germanium is added to the solder. The standard formation free energy of germanium oxide is lower than that of tin oxide. It will oxidize to germanium oxide before tin, effectively reducing the oxidation rate of the solder. At the same time, germanium also has a high affinity for oxygen and skin effect, forming a barrier layer on the surface of the molten solder to prevent further oxidation of the solder.

[0016] The soldering flux comprises the following components in percentage by mass:

[0017]

[0018] Rosin and liquid sweet gum are selected as one of the main components of the soldering flux of the present invention because rosin resin and sweet gum resin have good anti-oxidation effect at high temperature. The softening point of rosin is 70-80℃, the acid value is 150-180mgKOH / g, and it has high anti-oxidation property. It acts as a protective film at room temperature and is not active, but its activity is activated at high melting temperature, and the oxide film on the surface of the solder and the base material is quickly removed in a very short time. At the same time, a protective film is formed on the solder surface to prevent metal reoxidation, which is conducive to inhibiting the formation of the oxide film on the solder surface, so that the solder paste can still maintain good welding activity under continuous high-temperature baking; liquid sweet gum releases volatile oil at high temperature, effectively isolates air from contacting the solder surface, and effectively inhibits the formation of oxide film; the composition of sweet gum resin is similar to that of rosin resin; the present invention finds that the natural resin after mixing has a synergistic effect to improve the antioxidant effect of the resin as a whole, and more effectively removes solder slag and oxide film.

[0019] The active agent includes dimer fatty acid, boric anhydride and triethanolamine;

[0020] The dispersant is at least one of oleic acid amide, vinyl bis stearic acid amide and polyacryloyl dimethyl ammonium taurate.

[0021] Preferably, the mass ratio of the dimer fatty acid, boric anhydride and triethanolamine is (2-3): 1: (1-2). The active agent of the present invention is preferably a combination of dimer fatty acid, boric anhydride and triethanolamine. The dimer fatty acid has the advantages of high activity and minimal corrosivity. The role of triethanolamine is as an acidity regulator, and acid-base composite neutralization reaction occurs with dimer fatty acid at room temperature to prevent the precipitation of organic acid of the active agent at low temperature from weakening the activity of the soldering flux; during fusion welding, the temperature continues to rise, and the composite product is rapidly decomposed into dimer fatty acid and triethanolamine, and both are active agents, which improves the activity of the soldering flux; boric anhydride reacts with dimer fatty acid under alkaline conditions, exists in the form of borate ions, reduces oxides such as tin oxide and tin dioxide on the surface of the molten solder, effectively removes oxide welding slag, and forms a boron oxide protective layer to prevent the solder in the molten state from being oxidized again, thereby improving the wettability between the solder and the pad, promoting the wettability of the welding interface to form an excellent welding effect, so that the solder still maintains excellent welding activity under continuous high temperature baking.

[0022] Preferably, the antioxidant is at least one of ethoxyquinoline, 2-methylimidazole, benzimidazole and 2-ethylimidazole, which can prevent the soldering flux from being oxidized and deteriorated.

[0023] Preferably, the solvent is at least one of ethylene glycol dimethyl ether, triethylene glycol methyl ether and triethylene glycol dimethyl ether.

[0024] Preferably, the solder alloy powder has a particle size of ≤50 μm, and the content of particles with a particle size of ≤20 μm is 50 wt% or more. The particle size of the solder alloy powder is controlled below 50 microns, which can effectively improve the dispersion of the lead-free welding rod components after mixing; due to the differences in density and addition amount between the components, the dispersion degree will be low during the mixing process; preferably a small particle size can overcome the problem of uneven dispersion during the preparation of the welding rod.

[0025] Preferably, the metal impurity content of the tin is ≤0.01%.

[0026] In a second aspect, the present invention discloses a method for preparing the above-mentioned highly anti-oxidative lead-free solder paste, comprising the following steps:

[0027] (1) Weigh each component according to the formula and set aside;

[0028] (2) Add the solvent into a container, heat it to 110-130°C, then add rosin and stir until the rosin is completely dissolved;

[0029] (3) lowering the temperature to 50-80° C., adding liquid sweetgum, an activator, and an antioxidant, maintaining the temperature and stirring for 20-30 minutes to obtain a soldering flux;

[0030] (4) The temperature is maintained at 60-80° C., the flux obtained in step (3), the solder alloy powder and the dispersant are added to a solder paste mixer, the mixture is mixed and stirred for 30-60 minutes, the mixture is placed in a mold, the temperature is quickly lowered to 0-5° C., and the mold is refrigerated to obtain the highly antioxidant lead-free solder paste.

[0031] Preferably, the stirring speed in step (3) is 300-500 r / min.

[0032] Preferably, the stirring speed in step (4) is 1000-1500 r / min.

[0033] Beneficial effects of the present invention:

[0034] 1. Adding a certain amount of red phosphorus and germanium to the solder alloy powder disclosed in the present invention has no significant effect on the melting temperature of the solder alloy, but reduces the slag production and improves the oxidation resistance of the lead-free solder.

[0035] 2. The addition of liquid maple resin in the present invention can improve the synergistic antioxidant effect with rosin resin, significantly reduce the slag production, and strengthen the antioxidant protection of the overall resin flux on the welding alloy.

[0036] 3. The active agent component disclosed in the present invention has excellent antioxidant effect, significantly reduces the slag production, has less corrosiveness to solder and welding materials, and at the same time improves the wettability and expansion rate of the solder. DETAILED DESCRIPTION

[0037] The technical solutions of the present invention will be described clearly and completely below in combination with the embodiments and comparative examples of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments.

[0038] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.

[0039] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to explain the present invention and are not used to limit the present invention.

[0040] In the present invention:

[0041] Pure tin was purchased from Guangdong Wengjiang Chemical Reagent Co., Ltd., with a metal impurity content of ≤0.01%.

[0042] Rosin was purchased from Shanghai Yuanye Biotechnology Co., Ltd.

[0043] Liquid Liquidambar was purchased from Shanghai Yuanye Biotechnology Co., Ltd.

[0044] Preparation of Examples and Comparative Examples

[0045] Step (1), weigh each component according to the mass fraction and mass percentage in Table 1-3 and set aside;

[0046] Step (2), adding a solvent into a container, heating to 110-130° C., then adding rosin, and stirring until the rosin is completely dissolved;

[0047] Step (3), lowering the temperature to 50-80° C., adding liquid sweetgum, an active agent, and an antioxidant, maintaining the temperature and stirring at a speed of 300-500 r / min for 20-30 minutes to obtain a soldering flux;

[0048] Step (4), the temperature is maintained at 60-80°C, the flux obtained in step (3) and the solder alloy powder and the dispersant are added to a solder paste mixer, mixed and stirred at a speed of 1000-1500 r / min for 30-60 minutes, placed in a mold, and the temperature is quickly lowered to 0-5°C for molding and refrigeration to obtain a highly antioxidant lead-free solder paste embodiment and a comparative example.

[0049] Table 1 Welding alloy powder composition ratio

[0050] Component\Group Welding alloy powder 1 Welding alloy powder 2 Welding alloy powder 3 Welding alloy powder 4 Welding alloy powder 5 silver(%) 3.7 2.5 3.7 3.2 3.2 copper(%) 1.7 1.1 1.7 1.5 1.5 bismuth(%) 2.3 1.5 2.3 2.3 2.3 antimony(%) 1.4 0.9 1.4 0.9 0.9 Red phosphorus (%) 0.015 0.010 0.010 0.012 0 germanium(%) 0.010 0.005 0.005 0.009 0 tin(%) margin margin margin margin margin

[0051] Table 2 Flux composition ratio

[0052]

[0053]

[0054] Table 3 Proportions of components (mass fractions) in the examples and comparative examples

[0055]

[0056] Note: A space means nothing is added.

[0057] Performance Testing

[0058] Sample wettability determination:

[0059] The test results are shown in Table 4.

[0060] Sample expansion rate determination:

[0061] The test results are shown in Table 4.

[0062] Corrosion resistance determination:

[0063] The test results are shown in Table 4.

[0064] Dynamic slag rate determination:

[0065] According to SJ / T 11319-2005 “Quantitative Test Method for the Amount of Oxidation Slag in Tin Solder under Dynamic Conditions”, 2000g solder was subjected to a dynamic test at 270℃ for 8h on a wave soldering machine. The oxidized slag on the surface of the solder was scraped off and then physically separated through a sieve to obtain powdered tin ash. The powder was accurately weighed with an analytical balance and the data was recorded. The antioxidant performance was evaluated by the tin ash yield. The results are shown in Table 4.

[0066] Melting temperature determination:

[0067] The melting temperatures of Examples 1-5 and Comparative Examples 1-3 were measured using a differential calorimeter (DSC, TA-Q20). The sample weight was 5 mg. Before the test, the sample was placed in an ultrasonic cleaner and cleaned with deionized water for 5-10 minutes, then cleaned with alcohol and acetone solutions and dried in turn to ensure the accuracy of the test results. High-purity nitrogen was used as the protective atmosphere during the measurement process. The analysis temperature range was 25-300°C, and the heating rate and cooling rate were both 10°C / min. The results are shown in Table 4.

[0068] Table 4 Performance test results of examples and comparative examples

[0069] Test Items\Groups Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 Comparative Example 2 Comparative Example 3 Wettability 71 72 70 72 71 72 71 65 Expansion rate (%) 79.20 80.10 80.30 79.50 79.40 80.20 79.60 75.20 Corrosion resistance none none none none none none none slight Slag rate (%) 0.46 0.46 0.43 0.45 0.42 0.56 0.63 0.71 Melting temperature(℃) 219.1 218.6 218.7 219.1 219.1 218.7 219.6 218.9

[0070] Note: The melting temperature is the average of the starting melting temperature and the final melting temperature, and the melting range is not taken into consideration.

[0071] Analysis results:

[0072] According to the results of Examples 1-5 and Comparative Example 1, adding a certain amount of red phosphorus and germanium has no significant effect on the melting temperature of the solder alloy, but significantly reduces the slag production and improves the oxidation resistance of the lead-free solder.

[0073] According to the results of Example 5 and Comparative Example 2, the addition of liquid sweet gum in the present invention can improve the synergistic antioxidant effect with rosin resin, significantly reduce the slag production, and enhance the antioxidant protection of the overall resin flux to the welding alloy;

[0074] According to the results of Example 5 and Comparative Example 3, the active agent component added in the present invention has excellent antioxidant effect, significantly reduces the slag production, has less corrosion to solder and welding materials, and at the same time improves the wettability and expansion rate of the solder.

[0075] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A highly anti-oxidation lead-free solder paste, characterized in that: The composition includes the following components in parts by weight: 80-90 parts of welding alloy powder; 7-10 parts of flux; 3-5 parts of dispersant; The solder alloy powder comprises the following components in percentage by mass: The soldering flux comprises the following components in percentage by mass: The active agent includes dimer fatty acid, boric anhydride and triethanolamine; The dispersant is at least one of oleic acid amide, vinyl bis stearamide, and polyacryloyl dimethyl ammonium taurate; The mass ratio of the dimer fatty acid, boric anhydride and triethanolamine is (2-3):1:(1-2).

2. The highly anti-oxidation lead-free solder paste according to claim 1, characterized in that: The antioxidant is at least one of ethoxyquinoline, 2-methylimidazole, benzimidazole and 2-ethylimidazole.

3. The highly anti-oxidation lead-free solder paste according to claim 1, characterized in that: The solvent is at least one of ethylene glycol dimethyl ether, triethylene glycol methyl ether and triethylene glycol dimethyl ether.

4. The highly anti-oxidation lead-free solder paste according to claim 1, characterized in that: The particle size of the solder alloy powder is ≤50 μm, wherein the particle size is ≤20 μm and the content is 50 wt% or more.

5. The highly anti-oxidation lead-free solder paste according to claim 1, characterized in that: The metal impurity content of the tin is ≤0.01%.

6. The method for preparing a highly anti-oxidative lead-free solder paste according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) Weigh each component according to the formula and set aside; (2) Add the solvent into a container, heat it to 110-130°C, then add rosin and stir until the rosin is completely dissolved; (3) lowering the temperature to 50-80° C., adding liquid sweetgum, an activator, and an antioxidant, maintaining the temperature and stirring for 20-30 minutes to obtain a soldering flux; (4) The temperature is maintained at 60-80° C., the flux obtained in step (3), the solder alloy powder and the dispersant are added to a solder paste mixer, the mixture is mixed and stirred for 30-60 minutes, the mixture is placed in a mold, the temperature is quickly lowered to 0-5° C., and the mold is refrigerated to obtain the highly antioxidant lead-free solder paste.

7. The method for preparing a highly anti-oxidative lead-free solder paste according to claim 6, characterized in that: The stirring speed in step (3) is 300-500r / min.

8. The method for preparing a highly anti-oxidative lead-free solder paste according to claim 6, characterized in that: The stirring speed in step (4) is 1000-1500r / min.

Citation Information

Patent Citations

  • Quaternary Pb-free solder composition incorporating Sn-Ag-Cu-In

    CN101569965A

  • High-activity lead-free solder paste and preparation method thereof

    CN113441865A